Pengaturan Pengaturan Perizinan Penyelenggaraan Pelayanan Kesehatan Berbasis Online Di Indonesia - Ayu, Endang Putri; Budhiartie, Arrie; Fauzani Raharja, Ivan (Fakultas Hukum Universitas Jambi, 2022)
The development of increasingly advanced technology has spread to the health sector which is marked by the existence of online-based health services that can be done remotely without having to meet face-to-face. The use of online-based health services has increased due to the Covid-19 pandemic. However, the licensing for the implementation of online-based health services is still unclear, Article 4 paragraph (2) PP No. 47 of 2016 concerning Health Service Facilities states that